"Just transition" in India and fiscal stance: Analyzing the tax buoyancy of the extractive sector - Lekha Chakraborty; Emmanuel Thomas (Levy Economics Institute of Bard College, 2024)
Against the backdrop of fiscal transition concomitant to energy transition policies with climate change commitments, revenue from the extractive sector needs a recalibration in the subnational fiscal space. Extractive tax is the payment due to the government in exchange for the right to extract the mineral substance. Extractive tax has been fixed and paid in multiple tax regimes, sometimes on the measures of ad valorem (value-based) or profits or as the unit of the mineral extracted. Using the ARDL methodology, this paper analyzes the buoyancy of extractive revenue across the states in India, for the period 1991-92 to 2022-23 and analyzes the short- and long-run coefficients and their speed of adjustment. There are no identified structural breaks in the series predominantly because of the homogenous extractive policy regime shift to ad valorem from a unit-based regime. Our findings revealed that extractive tax is a buoyant source of own revenue, though there are distinct state-specific differentials. The policy implication of our study is crucial for a "just transition" related to climate change commitments where extractive industries' tax buoyancy is compared to other tax buoyancy across Indian states, and can be used as the base scenario to estimate the loss of revenue when fiscal transition sets in with "just transition" policies.
Keywords: Q40; Q48; E62; 330; fiscal rules; energy transition; tax buoyancy; ARDL; extractive sector regime